Rising wage inequality, the decline of collective bargaining, and the gender wage gap - Dirk Antonczyk; Bernd Fitzenberger; Katrin Sommerfeld (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This paper investigates the increase in wage inequality, the decline in collective bargaining, and the development of the gender wage gap in West Germany between 2001 and 2006. Based on detailed linked employer-employee data, we show that wage inequality is rising strongly – driven not only by real wage increases at the top of the wage distribution, but also by real wage losses below the median. Coverage by collective wage bargaining plummets by 16.5 (19.1) percentage points for male (female) employees. Despite these changes, the gender wage gap remains almost constant, with some small gains for women at the bottom and at the top of the wage distribution. A sequential decomposition analysis using quantile regression shows that all workplace related effects (firm effects and bargaining effects) and coefficients for personal characteristics contribute strongly to the rise in wage inequality. Among these, the firm coefficients effect dominates, which is almost exclusively driven by wage differences within and between different industries. Labor demand or firm wage policy related effects contribute to an increase in the gender wage gap. Personal characteristics tend to reduce wage inequality for both, males and females, as well as the gender wage gap.
Keywords: J31; J51; J52; C21; 330; Distribution; Gender Wage Gap; Collective Bargaining; Quantile Regression; Sequential Decomposition; Lohnstruktur; Tarifpolitik; Lohndifferenzierung; Arbeitsplatz; Qualifikation; Schätzung; Deutschland